Global citizenship education and the subversion human injustices: A philosophical inquiry - August-Mowers, C. M.; Waghid, Y. (South African Journal of Higher Education, 2026)
Literature on Global Citizenship Education (GCE) abounds, spanning a wide range of theoretical, pedagogical, and policy perspectives. Our own work accentuates GCE as an autonomous, deliberative, and decolonial praxis aimed at cultivating social and democratic justice through critical engagement and ethical responsibility. Yet, when one surveys the existing body of scholarship on global human injustices, what emerges is a sobering pattern of persistent and systemic violations of human rights, particularly evident in regions such as Northern Africa, Palestine, and Ukraine. These contexts expose the tensions between the aspirations of GCE and the realities of structural violence and geopolitical domination. In this article, we therefore revisit and reconceptualise a plausible notion of GCE, arguing that the continuing atrocities and gross human rights violations across the world undermine the legitimate enactment and transformative potential of GCE as a vehicle for justice and solidarity.